Utilizing a Manualized Therapy to Provide Parallel Treatment to Older Adults With Cancer and Their Caregivers: A Case Study. (February 2022) - Stern, Amy; Hershkowitz, Robin; Trevino, Kelly M.
The experience of anxiety is a common and understandable reaction to a diagnosis of and treatment for cancer. Patients of any age may experience negative psychological and physical symptoms during cancer treatment; older adults with cancer simultaneously face the impact of cancer and the effects of aging. Caregivers of older adults with cancer are also vulnerable to experiencing anxiety as their loved one navigates the physical and emotional sequelae of their illness and treatment. This article describes the use of Managing Anxiety from Cancer (MAC), a seven-session telephone-delivered manualized cognitive behavioral intervention that includes strategies from acceptance and commitment therapy and problem-solving therapy, with an older woman with cancer and her adult daughter. MAC includes a variety of techniques for patients and caregivers, who are encouraged to use these strategies individually or in different combinations to manage their anxiety. This brief treatment provided a parallel experience for the participants, as the older adult patient and her caregiver were taught the same anxiety-management techniques by their individual therapists. We will discuss the advantages and drawbacks of using a manualized psychotherapy intervention in this case, as well as MAC's impact on each member of this pair and on the dyad as a unit. Both individuals reported experiencing benefits from MAC and identified MAC-acquired skills they planned to use in the future to manage their anxiety and improve communication. While assessment data did not reflect a decrease in anxiety, it is possible that the stress of the COVID-19 pandemic confounded these data.